Continuous composite finite-time convergent guidance laws with autopilot dynamics compensation. (September 2015) - He, Shaoming; Lin, Defu
Abstract: This paper has proposed two continuous composite finite-time convergent guidance laws to intercept maneuvering targets in the presence of autopilot lag: one is for hit-to-kill and the other is for zeroing the line-of-sight (LOS) angular rate. More specifically, the nonlinear disturbance observer (NDOB) is used to estimate the lumped uncertainty online while the finite-time control technique is used to fulfill the design goal in finite time. The key feature in derivation of the proposed guidance law is that two integral-type Lyapunov functions are used to avoid analytic differentiation of virtual control law encountered with traditional backstepping. The finite-time stability of the closed-loop nonlinear observer-controller system is established using finite-time bounded (FTB) function and Lyapunov function methods. Numerical simulations with some comparisons are carried out to demonstrate the superiority of the proposed method. Highlights: Two composite continuous finite-time convergent guidance laws are presented for intercepting maneuvering targets in the presence of autopilot lag. The proposed guidance laws are derived through a combination of nonlinear disturbance observer technique and backstepping-like approach. The finite-time stability of the closed-loop guidance system is proved via finite-time bounded function and Lyapunov function methods. Simulation results with some comparisons demonstrate the effectiveness of the proposed method.